Mechanical Properties of Dissimilar A356/SAPH440 Lap Joints by the Friction Stir Spot Welding and Self-Piercing Riveting - Bang, Han Sur; Lee, W.R.; Hong, S.M.; Lee, S.Y.; Song, J.H.; Kim, J.M.; Bang, Hi Seon (Проблемы прочности, 2018)
Aluminum alloy A356-T6 and automotive steel sheet SAPH440 were joined using friction stir spot welding and self-piercing riveting. The maximum tensile shear strength values in weld joints were approximately 3.5 kN at a rotation speed of 500 rpm and plunge depth of 1.0 mm. It was confirmed that the intermetallic compound layer of weld joints below 9.23 m did not exceed the permissible thickness 10 m of Al–Fe joints. The self-piercing riveting joints exhibited maximum tensile- shear strength of 7.9 kN, which was higher than that of the weld joints. However, during the riveting process, cracking appeared in the joint on the aluminum side, which was caused by lack of ductility of cast aluminum. In addition, it was observed that the cracks on the aluminum side were getting larger, as the radius of the lower mold increased.